2012
DOI: 10.5194/hess-16-1947-2012
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of herbicide mobilisation and transport at catchment scale: insights from a field experiment

Abstract: During rain events, herbicides can be transported from their point of application to surface waters, where they may harm aquatic organisms. Since the spatial pattern of mobilisation and transport is heterogeneous, the contributions of different fields to the herbicide load in the stream may vary considerably within one catchment. Therefore, the prediction of contributing areas could help to target mitigation measures efficiently to those locations where they reduce herbicide pollution the most. <br&… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 48 publications
3
105
1
Order By: Relevance
“…Inflow of water and pesticides from upstream parts was not considered in this model. The hillslope is convex with an average gradient of 5 %, which is comparable to the average slope in previously studied agricultural catchments (Doppler et al, 2012;Leu et al, 2004a). A river bank was incorporated as a vertical drop of 2 m over the last 5 m in the x direction, which increased the average slope to 5.8 %.…”
Section: Hillslope Geometry and Model Gridmentioning
confidence: 54%
See 1 more Smart Citation
“…Inflow of water and pesticides from upstream parts was not considered in this model. The hillslope is convex with an average gradient of 5 %, which is comparable to the average slope in previously studied agricultural catchments (Doppler et al, 2012;Leu et al, 2004a). A river bank was incorporated as a vertical drop of 2 m over the last 5 m in the x direction, which increased the average slope to 5.8 %.…”
Section: Hillslope Geometry and Model Gridmentioning
confidence: 54%
“…Surface runoff in scenario 2 occurred as infiltration excess overland flow, which can be an important mechanism of pesticide transport from agricultural land (Doppler et al, 2012). The infiltration excess overland flow was generated by increasing the coupling length from 0.1 m to 0.8 m, which decreased the coupling between overland flow domain and subsurface domain.…”
Section: Responses To Rainfall Eventsmentioning
confidence: 99%
“…Thus, long-term, seasonal or event-based monitoring of river water quality (i.e., solutes used as environmental tracers) provides valuable information about the source zones of catchment streamflow (e.g., quickflow, baseflow) and groundwater-surface water interaction processes (e.g., Cook and Herczeg, 2000;Leibundgut and Seibert, 2011). In association with agricultural land use, various studies found a rapid and significant increase of nutrient export rates when potential source areas become hydrologically connected to the river system during rainfall events (e.g., Doppler et al, 2012;Ocampo et al, 2006;Stieglitz et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The application of S-metolachlor and terbuthylazine in Ossingen, for example, took place just before an intensive precipitation event. Through direct shortcuts, such as manholes of drainage systems and storm drains, the transfer to the river was accelerated and very high concentrations were measured (Doppler et al, 2012).…”
Section: Metricmentioning
confidence: 99%
“…Such studies are rare and we used the following studies situated in the north-eastern part of Switzerland. The sampling campaigns from Gomides Freitas et al (2008) and Doppler et al (2012) measured herbicide concentrations at the small-scale agricultural catchments Summerau and Ossingen, respectively, after a controlled herbicide application. Wittmer et al (2010) monitored the mass and dates of herbicide applications in a slightly larger catchment, Mönchaltorf (25 km 2 ), with mixed land use.…”
Section: Calibration Sitesmentioning
confidence: 99%